Advancing Indigenous self-determination and health equity: Lessons from a failed Australian public policy - Toby Freeman; Belinda Townsend; Tamara Mackean; Connie Musolino; Sharon Friel; Fran Baum (Elsevier, 2022)
The 2007 Northern Territory Emergency Response (NTER) targeted Aboriginal communities in the Northern Territory in Australia. The NTER imposed draconian measures unfavourable to health, contributing to health inequities. There is little research investigating why the NTER was framed so negatively, and how this framing passed into legislation so unassailably. We used institutional theory to understand what factors contributed to the NTER agenda framing, what institutional factors enabled its dominance over pro-equity frames, and what lessons can be learned for future efforts to improve public policies for health equity. We interviewed 21 key policy actors, including actors with a role in the NTER, government opposition, Aboriginal civil society, non-Indigenous stakeholders, and actors from the Little Children Are Sacred report and Northern Territory government, and the Coalition of Aboriginal Organisations that provided alternative pro-equity policy framings that were not taken up. We found Federal government framing was driven by a deficit discourse of Aboriginal and Torres Strait Islander peoples in the media, and the Federal government's interest in winning the upcoming election, trialling welfare reform, and gaining more control over Northern Territory Indigenous Affairs. The framing passed almost unchanged into legislation because of the government's closed processes that excluded Aboriginal perspectives, the media's failure to report dissenting Aboriginal voices, and the power the Federal government was able to wield over the Northern Territory. The most critical action needed for more pro-equity Indigenous Affairs policy is resourced structures to provide more structural power for Aboriginal and Torres Strait Islander people to influence policy.